Efektivitas Komitmen Organisasi Dalam Peningkatkan Kinerja Pegawai Dari Aspek Kepuasan Kerja, Budaya Organisasi, Disiplin Kerja Pada Badan Keuangan Kabupaten Ngawi - Nanik Lis Iswahyuti; Ifah Lathifah (STIE AUB Surakarta, 2026)
The purpose of this study is to determine, test and analyze the effectiveness of organizational commitment in improving employee performance at the Ngawi Regency Financial Agency. Respondents in this study were 80 employees at the Ngawi Regency Financial Agency. The analysis technique in this study is multiple linear regression path analysis. The results of the study show that job satisfaction has a significant effect on organizational commitment. Organizational culture has a significant effect on organizational commitment. Work discipline has no significant effect on employee organizational commitment. Job satisfaction has no significant effect on employee performance. Organizational culture has a significant effect on employee performance. Work discipline has a significant effect on employee performance. Organizational commitment has a significant effect on employee performance. The results of the F test show that the value of F = 153.205 is significant with a significance of 0.000 <0.05. So it can be concluded that together the variables of job satisfaction, organizational culture, work discipline and organizational commitment have a significant effect on employee performance at the Ngawi Regency Financial Agency. The total R2 value of 0.959 means that employee performance at the Ngawi Regency Finance Agency is explained by the variables of job satisfaction, organizational culture, work discipline, and organizational commitment by 95.9%, and the remaining 4.1% is explained by other variables outside the research model, for example, competence and work stress. By looking at the results of the analysis, both direct and indirect influences, the direct influence of organizational culture on performance is the most effective or dominant influence on performance when compared to other paths.